A theoretical overview of road hump effects on traffic speed in residential environments - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (Malaysian Institute of Planners, 2016)
This paper is part of an ongoing study to analyse the effectiveness of road humps as a traffic calming measure in improving the residential living environment. A review was conducted on various literatures concerning the effects of road humps on vehicle speeds, particularly in residential areas. The major findings from the literatures are that the vehicles’ operating speeds are affected by the hump design and spacing in between humps. An incorrect hump profile will also potentially result in passenger discomfort and vehicle damage. Public perceptions also agreed that road humps are effective in reducing vehicle speeds. More studies should link field study results with residents’ perceptions particularly in Malaysia, while considering the effect of road geometrics and other devices possibly impacting vehicle speeds along selected roads. Further research also needs to be done to test the effectiveness of current schemes in Malaysian residential areas, as many are on an ad-hoc basis.